English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1) Simplify:
sqrt(250y^6)

2) Simplify:
sqrt(12x^3/5)

3) Simplify by combining like terms:
5sqrt8 + 2sqrt18

4) Solve:
sqrt (2y +7) +4 = y

5) Solve:
sqrt(48 - 2y) = y

2006-11-12 11:26:55 · 3 answers · asked by Big Daddy 2 in Science & Mathematics Mathematics

3 answers

I'll do the first one. The others are the same

SQRT(250*y^6) = SQRT(250) * SQRT(y^6)
= SQRT(25)*SQRT(10)*y3
= 5*SQRT(10)*y^3

2006-11-12 11:32:43 · answer #1 · answered by Dr. J. 6 · 0 0

1) Simplify:
sqrt(250y^6)
sqrt(25y^6)*sqrt(10)
5y^3*sqrt(10)

2) Simplify:
sqrt(12x^3/5)
sqrt(4x^2)*sqrt(3x/5)
2x*sqrt(3x/5)

3) Simplify by combining like terms:
5sqrt8 + 2sqrt18
10*sqrt(2)+6*sqrt(2)
16*sqrt(2)

4) Solve:
sqrt (2y +7) +4 = y
2y+7=(y-4)^2
2y+7=y^2-8y+16
0=y^2-10y+9
(y-9)(y-1)=0
y=9
y=1

5) Solve:
sqrt(48 - 2y) = y
48-2y=y^2
y^2+2y-48=0
(y+8)(y-6)=0
y=-8
y=6

2006-11-12 20:56:05 · answer #2 · answered by yupchagee 7 · 0 0

1) sqrt(250y^6)=sqrt(25 x 10 x y^6) = 5sqrt(10y^6) =5y^3sqrt(10)

2)sqrt(12x^3/5)=sqrt(4 x 3 x x^(6/10) ) = 2(x^3/10) x sqrt(3)

3)5sqrt(8)+2sqrt(18) = 5sqrt(4x2) + 2sqrt(9x2) = 5(2)sqrt(2) + 2(3)sqrt(2) = 10sqrt(s) + 6sqrt(2) = 16sqrt(2)

4)sqrt(2y+7)+4=y
subtract 4 from both sides: sqrt(2y+7)=y-4
now square both sides: 2y+7= y^2 - 8y +16
and simplify: y^2 -10y +9 = 0
and factor: (y-9)(y-1)=0

5) sqrt(48-2y)=y
square both sides: 48-2y=y^2
simplify: y^2 + 2y - 48 = 0
factor: (y-6)(y+8)=0

2006-11-12 19:40:50 · answer #3 · answered by kellenraid 6 · 0 0

fedest.com, questions and answers